Glyphosate dynamics prediction in a soil under conventional and Nno-tillage systems during the crop cycle - Villarreal, Rafael (2020)
Simulation models are efficient tools in order to predict the fate of different solutes in agricultural soils. The objectives of this work were to compare measured and predicted glyphosate and AMPA (its main metabolite) content values in a soil under no tillage, NT, and conventional tillage, CT; and to compare the predictions considering constant and time-variable hydraulic properties. Additionally, we evaluated the ability of the model to predict glyphosate and AMPA accumulation during the crop cycle. Hydrus 1-D code was used in order to predict the glyphosate and AMPA dynamics, considering constant and time?variable hydraulic properties during the studied crop cycle. In general, the prediction of glyphosate and AMPA distribution along the soil profile using HYDRUS 1-D was satisfactory; however an overestimation of both compounds was observed in the first 20 cm of the soil probably because of the preferential flow. Additionally, the accumulation process of glyphosate and AMPA in the soil during the crop cycle was underestimated by HYDRUS 1-D, as compared with the observed field data. Simulated data show that higher values of K0 increase the risk of glyphosate and AMPA vertical transport. The inclusion of temporal variation of hydraulic properties in glyphosate and AMPA simulation did not improve the simulation performance, showing that the model is more sensitive to the parameters related to the solutes. From the obtained results, HYDRUS 1-D code allowed to predict glyphosate and AMPA dynamics reasonably well in agricultural soils of the Argentinean Pampas region and is a potential model to give support in the analysis of environmental risk of leaching and soil contamination.